3D meso-scale modelling of tensile and compressive fracture behaviour of steel fibre reinforced concrete. (1st July 2022) - Naderi, Sadjad; Zhang, Mingzhong
Abstract: This paper presents a novel meso-scale modelling framework to investigate the fracture process in steel fibre reinforced concrete (SFRC) under uniaxial tension and compression considering its 3D mesostructural characteristics, including different types of fibres, realistic shaped aggregates, mortar, interfacial transition zone and voids. Based on a hybrid damage model consisting of cohesive element method and damage plasticity method, a cost-effective finite element approach was proposed to simulate the fracture behaviour of SFRC in terms of stress–strain response, energy dissipation and crack morphology. The results indicated that under given conditions, the straight and hooked-end fibres improved the compressive damage tolerances of concrete over 11.5% while the spiral fibres had a negligible effect of 2.6%. The tensile macro-damage level index introduced was reduced over 15% by all fibres. Compared to straight fibres, the higher anchoring capacity of spiral fibres reduced the reinforcement performance while hooked-end fibres did not exhibit a significant influence.